The synthesis, photophysical and biological evaluation of Novel Bis(1,8-naphthalimides) - Gillespie, Lisa Jane (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
Chapter One provides a review of 1,8-naphthalimide research and, in particular, the exploration of such compounds as anti-cancer agents. Advances in anti-cancer therapeutics and targeting of DNA are also discussed. A description of the recent developments in bisnaphthalimide and naphthalene diimide structures as potential anti-tumour agents, DNA binders and DNA probes is provided. The background for this research project is discussed in detail. This project sought to design and create two novel families of bisnaphthalimides along with the necessary monopeptide and dipeptide functionalised mononaphthalimides and spacer systems en route. Conventional and new synthetic ideas and syntheses would be employed. These systems are intended as DNA binders and potential anti-cancer agents. The design and synthetic plan for the development of these novel families of naphthalene diimide linked bisnaphthalimides is illustrated. A 'tail-to-tail' bisnaphthalimide family was planned by tethering two compounds via the 4-position through a naphthalene diimide spacer. A 'head-to-head' bisnaphthalimide family was designed by tethering two compounds via a peptide functionalisation possessing a free terminal amine through a naphthalene diimide spacer. All these bisnaphthalimides would be symmetrical. The aims of this project are discussed and include the achievement of some degree of sequence selectivity in DNA binding, the observation of the effect on binding of altering the length of a spacer, the enhancement of binding over that of mononaphthalimides and the demonstration of anti-cancer activity.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin